DEVELOPING PICTURE SERIES AS A MEDIA FOR TEACHING WRITING PROCEDURE TEXT AT THE THIRD YEAR STUDENTS OF PAHLAWAN NASIONAL JUNIOR HIGH SCHOOL - Ratnaeza Syahputra Nst.; Sumarsih Sumarsih; Rafika Dewi Nasution (Universitas Negeri Medan, 2017)
The aim of this study is to develop Picture Series as a media for teaching writing procedure text at the third year students of Pahlawan Nasional Junior High School. The researcher used Research and Development (R &D) method through ten steps: observing, evaluating need analysis, developing first media, validating with experts, revising it, testing in small group, revising, testing in large group, revising, producing final product. The subjects of this research were 30 students from IX-1 class, and 34 students from IX-2 class. The instrument of collecting data was using questionnaires. The data were analyzed by descriptive text technique. The result of the product from two validators – an English lecturer from State University of Medan and an English teacher from Pahlawan Nasional Junior High School, was in scale of 4 which was in good quality. And the result from all of the students was in scale of 4 which was in good quality too. It means that the developed product/Picture Series is eligible to be used for teaching writing procedure text for the third year students in Pahlawan Nasional Junior High School. Keywords: Research and Development (R & D), writing procedure text, picture series